A preparação do Ministério Público para a Justiça Constitucional no Brasil - Melo, Marconi Antas Falcone de (2012)
This work aims to investigate preparation on behalf of Brazilian Public Prosecution, for rational performance in Brazilian Constitutional Justice System. The research does not attempt to be a manual on constitutionality and rather aims to focus on the efficiency of preparation of the Brazilian Public Prosecution; which is its differential. The topic was chosen since the Public Prosecution is considered rather amateur regarding constitutionality issues. The main hypothesis was based on three pillars. The first one was related to the location of the Public Prosecution in the Brazilian legal, political as well as the legal- political sub-systems. This analysis permits a theoretical basis to legitimize specific constitutionality control in the constitutional justice system. In second place, the research aims to point out possible unconstitutionality and contradictory issues related to the Public Prosecution. These issues prevent efficient constitutional institutional action and involve themes such as member recruitment, unit principles, contradictions and redundancy present in secondinstances procedures in the Public Prosecution as well as allow rationalization of duties. The work also emphasizes the need or the creation of a Section for constitutional and action appeals. At the end, the research points out constitutionality control as well as other issues that acknowledge themes totally centered on the Brazilian Public Prosecution. The method used was of a focused research on legal science such as compared law and general theory of law. The theories were used since the theme requires comparative analysis in order to achieve consistent conclusions. On the other hand, the main fundaments used were Systems Theories according to Niklas Luhmann as well as other authors that deal with the topic. Some practical examples were used according to the Brazilian Supreme Court jurisprudence. Results show that there is a need for new laws regarding the matter as well as the promotion of legislative alterations so that the Public Prosecution is able to control constitutionality issues in an effective and satisfactory fashion so that it is able to rationally participate in the constitutional justice system